Thermal conversion of granules from feathers, meat and bone meal and poultry litter to ash with fertilizing properties - Staroń, Paweł; Kowalski, Zygmunt; Staroń, Anita; Banach, Marcin (Agricultural and Food Science, 2017)
Recently, the increased consumption of poultry meat in the EU has been observed. Short cycle of poultry meat production allows adjusting the level of production to demand. With the increase in the meat production the amount of generated waste that has to be disposed because they pose a risk to the environment also increases. The work presents the possibility to produce a mixture of feathers, meat-bone meal and poultry litter that can be used for energy purposes (alternative fuel). Moreover, the composition of the ashes after combustion will be similar to phosphorus-potassium fertilizers offered for sale. The resulting granules are characterized by a calorific value in the range 13.1–13.3 kJg-1. The ash after its combustion contained 11.33–13.38% of phosphorous, 4.94–5.67% of potassium, 31.85–32.69% of calcium and 2.07–2.51% of magnesium. Moreover, the ash contained 0.45-0.46% of iron, 0.10–0.11% of manganese, 0.11–0.14 of zinc and 0.02% of copper. Mineral combusted residue of this type of granules has a low content of heavy metals and can be used as an additive to fertilizers and soil improvers, in order to enrich their composition in valuable macro- and micronutrients.